Molecular Dynamics Simulation and Mechanical Property Analysis of Unsaturated Polyester/Glass Fiber Composites - Budi Ariani, Desi; Silvia; Shafwan Aziz, Malvin (Jurnal Serambi Engineering, 2025)
Composite materials are essential for engineering applications due to their superior mechanical properties. Unsaturated polyester reinforced with glass fiber is widely used but optimizing its mechanical performance remains challenging. This study combines experimental testing and molecular dynamics (MD) simulations to investigate the mechanical properties of unsaturated polyester/glass fiber composites. Composites were fabricated with varying glass fiber volume fractions, and their impact strength and density were tested. The results showed an optimal glass fiber fraction at 12.5%v, achieving the highest impact strength (142.80 kJ/m²) and increased density (1.4408 g/cm³). MD simulations validated these findings, highlighting the role of van der Waals forces in molecular aggregation and interfacial bonding. This study bridges experimental and MD computational insights, recommending the simulation of treated glass fiber in the future to explore the potential of treated glass fibers in enhancing the interfacial bonding and overall mechanical performance of unsaturated polyester/glass fiber composites.